WAKAF HAK CIPTA - Syufa'at Syufa'at (Jurnal Penelitian Agama, 2017)
Abstract : Waqf is one of the recommended forms of philanthropy (mandub) in Islam, because the reward of waqf will always flow even though wakif has died. In the modern era, waqf is no longer interpreted by giving immovable property such as land and buildings , but movable property can be used as a waqf object. One of the objects of immovable property is intellectual property rights which is copyright. With the existence of waqf copyright no longer obligate for the giver of waqf to have immovable property as treasure to be represented but other object which have economic value and social also can be waqf property. Keywords : Copyrights, Waqf